Association between benzodiazepine use and risks of chronic-onset poststroke pneumonia: a population-based cohort study. Issue 1 (25th January 2019) - Lin, Shu-Man; Yang, Shih-Hsien; Liang, Chung-Chao; Huang, Huei-Kai; Loh, Ching-Hui
Abstract : Objectives: To investigate the association between benzodiazepine (BZD) use and the risk of chronic-onset poststroke pneumonia. Design: Population-based propensity-matched retrospective cohort study. Setting: Taiwan's National Health Insurance Research Database. Participants: Patients newly diagnosed with stroke between 2000 and 2012 were identified and, after propensity score matching, 7516 patients were enrolled. Among these, 3758 patients received BZDs after stroke while 3758 did not. Outcome measures: HRs for developing pneumonia over 1 month after stroke according to BZD use were assessed using Cox proportional hazards regression models. Analyses according to cumulative defined daily doses (cDDDs) of BZDs and stratification for age and sex were also performed. Results: During a mean follow-up time of 4.4 years, 1027 patients in the BZD cohort and 478 patients in the non-BZD cohort developed pneumonia over 1 month after stroke. Patients using BZDs after stroke had a higher pneumonia risk than did those not using BZDs (52.2vs32.6 per 1000 person-years, adjusted HR (aHR)=2.21, 95% CI (CI)=1.97 to 2.48, p<0.001). Analyses based on cumulative BZD dose revealed that all BZD user subgroups were associated with a higher risk of pneumonia. The aHRs for patients taking 1–90, 91–365 and >365 cDDDs of BZDs were 2.28 (95% CI=2.01 to 2.58; p<0.001), 2.09 (95% CI=1.77 to 2.47; p<0.001) and 2.08 (95% CI=1.72 to 2.52; p<0.001), respectively. The significant association between BZD use and increased pneumonia risk persisted even after stratifying subgroups by age and sex. Conclusions: BZD use is associated with an increased risk of chronic-onset poststroke pneumonia.